2008
DOI: 10.2134/jeq2006.0550
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Fate of Nitrate at the Ground‐Water/Surface‐Water Interface

Abstract: Although numerous studies of hyporheic exchange and denitrification have been conducted in pristine, high‐gradient streams, few studies of this type have been conducted in nutrient‐rich, low‐gradient streams. This is a particularly important subject given the interest in nitrogen (N) inputs to the Gulf of Mexico and other eutrophic aquatic systems. A combination of hydrologic, mineralogical, chemical, dissolved gas, and isotopic data were used to determine the processes controlling transport and fate of NO3− i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 60 publications
5
111
0
1
Order By: Relevance
“…Maple Creek was identified and investigated by the USGS under the National Water-Quality Assessment Program in recent years as a representative agricultural headwater stream affected by farm-based chemicals (Fredrick et al 2006). The stream is characterized by shallow annual mean flows (2.27 m 3 s 21 ), sediment composed of fine sand and silt, and high nutrient loads (Fredrick et al 2006;Puckett et al 2008). The site was chosen for the present study due to flow and sediment conditions conducive to performing mesocosm experiments, availability of water quality and real-time gauging station data, and nutrient and temperature conditions favorable to biotic activity (Puckett et al 2008 The mesocosms were hollow cylinders made of SolacrylH SUVT (Spartech Company), standing 61 cm tall, with inner diameters of 46 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maple Creek was identified and investigated by the USGS under the National Water-Quality Assessment Program in recent years as a representative agricultural headwater stream affected by farm-based chemicals (Fredrick et al 2006). The stream is characterized by shallow annual mean flows (2.27 m 3 s 21 ), sediment composed of fine sand and silt, and high nutrient loads (Fredrick et al 2006;Puckett et al 2008). The site was chosen for the present study due to flow and sediment conditions conducive to performing mesocosm experiments, availability of water quality and real-time gauging station data, and nutrient and temperature conditions favorable to biotic activity (Puckett et al 2008 The mesocosms were hollow cylinders made of SolacrylH SUVT (Spartech Company), standing 61 cm tall, with inner diameters of 46 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The stream is characterized by shallow annual mean flows (2.27 m 3 s 21 ), sediment composed of fine sand and silt, and high nutrient loads (Fredrick et al 2006;Puckett et al 2008). The site was chosen for the present study due to flow and sediment conditions conducive to performing mesocosm experiments, availability of water quality and real-time gauging station data, and nutrient and temperature conditions favorable to biotic activity (Puckett et al 2008 The mesocosms were hollow cylinders made of SolacrylH SUVT (Spartech Company), standing 61 cm tall, with inner diameters of 46 cm. SolacrylH SUVT is a type of Plexiglas that is transparent to both visible and UV light; these properties were verified by determining light transmittance on a spectrophotometer prior to the field experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Where residence times are sufficiently long and there are potential electron donors available denitrification can occur in this zone (Puckett et al, 2008). Krause et al (2009) showed that the distribution of the low redox zone can be very variable.…”
Section: Surface Water Wetlands and Groundwater-dependent Ecosystemsmentioning
confidence: 99%
“…3 and Table 6). Many studies report that DNP is more strongly correlated with available carbon (e.g., microbially labile C) rather than total organic carbon (D' Angelo and Reddy, 1999;Hill and Cardaci 2002;Hernandez and Mitsch, 2007;Puckett et al, 2008). Only organic carbon was measured for this study, so it is possible that there may be substantial differences in carbon availability between the environments that may affect DNP.…”
Section: Denitrification In Wetlandsmentioning
confidence: 92%